An American trilogy : death, slavery, and dominion on the banks of the Cape Fear River - Wise, Steven M. (Da Capo Press, 2009)
Steven M. Wise, author of the acclaimed Though the Heavens May Fall, connects the near extinction of native peoples, slavery, and today's unfeeling slaughter of animals.